2011
DOI: 10.1002/hrm.20406
|View full text |Cite
|
Sign up to set email alerts
|

Employee voice and job satisfaction in Australia: The centrality of direct voice

Abstract: This study examines the relationship between employee voice and job satisfaction using data from the 2007 Australian Workplace Representation Survey (AWRPS) of 1,022 employees. Drawing on human resource management and industrial relations literature, we test hypotheses concerning the relationship between direct and union voice arrangements and job satisfaction. This relationship represents a gap in the literature, which is important from both theoretical and practical perspectives. Controlling for a range of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 58 publications
8
102
0
3
Order By: Relevance
“…Similarly, other research has found that involvement in decision-making processes can improve employee satisfaction (e.g. Boxall & Macky, 2014;Cox, Zagelmeyer, & Marchington, 2006;Holland et al, 2011;Macky & Boxall, 2008;Wood, 2008). Hence, we hypothesise the following:…”
Section: Employee Involvement and Job Satisfactionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, other research has found that involvement in decision-making processes can improve employee satisfaction (e.g. Boxall & Macky, 2014;Cox, Zagelmeyer, & Marchington, 2006;Holland et al, 2011;Macky & Boxall, 2008;Wood, 2008). Hence, we hypothesise the following:…”
Section: Employee Involvement and Job Satisfactionmentioning
confidence: 76%
“…These include practices that encourage involvement in decision-making and the development and exercise of problemsolving skills. Employee involvement practices have been shown to reduce job stress (Mackie, Holahan, & Gottlieb, 2001), increase job satisfaction and organisational commitment (Boxall & Macky, 2014;Holland, Pyman, Cooper, & Teicher, 2011;Macky & Boxall, 2008), and improve productivity and organisational performance (Wood, Van Veldhoven, Croon, & de Menezes, 2012).…”
Section: Employee Involvement and Job Satisfactionmentioning
confidence: 99%
“…In particular, as alluded to earlier, the Bvoice^mechanism has been promoted in the HRM literature as a productive way to address employee concerns and enhance organizational commitment (e.g., Colvin, 2004b;Farndale et al, 2011;Harlos, 2010;Holland, Pyman, Cooper, & Teicher, 2011). Commonly used voice methods in grievance management include, for example, open-door policy, exit interviews, employee opinion survey, and committee meetings.…”
Section: Approaches To Grievance Managementmentioning
confidence: 97%
“…Consistently, involvement has been regarded as a determinant of workers' satisfaction (Wood & Wal, 2007;Richardson, Danford, Stewart, & Pulignano, 2010). Research results, however, are not unequivocal on this aspect (Cox, Zagelmeyer, & Marchington, 2006;Diamantidis & Chatzoglou, 2011;Holland, Pyman, Cooper, & Teicher, 2011;Zatzik & Iverson, 2011).…”
Section: Hypothesis 3 Teamwork Has a Positive Impact On Firm Performmentioning
confidence: 99%